2016
DOI: 10.1177/0963721416656348
|View full text |Cite
|
Sign up to set email alerts
|

Can the Unconscious Boost Lie-Detection Accuracy?

Abstract: Recently, a variety of methods have been used to show that unconscious processes can boost lie-detection accuracy. This article considers the latest developments in the context of research into unconscious cognition. Unconscious cognition has been under attack in recent years because the findings do not replicate, and when they do show reliably improved performance, they fail to exclude the possibility that conscious processing is at work. Here we show that work into unconscious lie detection suffers from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Recent findings suggest that conscious processes can hinder the ability to detect deception (e.g., Reinhard et al, 2013a;Street and Vadillo, 2016). Judging whether a person is truthful or deceptive can be regarded as a complex decision.…”
Section: (Un)conscious Thought and Deception Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings suggest that conscious processes can hinder the ability to detect deception (e.g., Reinhard et al, 2013a;Street and Vadillo, 2016). Judging whether a person is truthful or deceptive can be regarded as a complex decision.…”
Section: (Un)conscious Thought and Deception Detectionmentioning
confidence: 99%
“…"; e.g., DePaulo et al, 1997;Ten Brinke et al, 2014). The claims that indirect measures outperform direct measures, however, are sometimes based on incomparable metrics (Levine and Bond, 2014;Franz and von Luxburg, 2015;Street and Vadillo, 2016;Levine, 2019b). Metaanalysis showed that most indirect measures do not outperform direct measures (Bond et al, 2014).…”
Section: (Un)conscious Thought and Deception Detectionmentioning
confidence: 99%
“…The 20 indirect measures that did not outperform direct measures include rating the pleasantness, expressiveness, and relaxation of the face, nervousness and friendliness. One explanation for why some indirect measures, but not others, outperform direct measures is that only indirect measures that focus observers' attention on deception cues that are useful can increase accuracy (Street & Richardson, 2015;Street & Vadillo, 2016). …”
Section: Detecting Deception From Emotional Expressionsmentioning
confidence: 99%
“…However, Anderson and colleagues demonstrated that their result was a methodological effect attributable to the fact that the scale used to collect explicit ratings was less sensitive than the one used for indirect ratings, an effect which has been found in a meta-analysis (Bond and DePaulo, 2006 ). In fact, indirect lie detection often performs worse than direct lie detection (Levine and Bond, 2014 ; Bond et al, 2015 ), and can be explained by entirely conscious processes (Street and Richardson, 2015 ; Street and Vadillo, 2016 ).…”
mentioning
confidence: 99%
“…A useful contribution of the tipping point theory, then, is to make explicit a number of predictions that could test for the presence of accusatory reluctance (see Box 1 ). But this exploration can take place without reference to an undefined hidden process (Street and Vadillo, 2016 ).…”
mentioning
confidence: 99%